Work environment standardization for the t-shirt production process at CV Nanda Konveksi using lean principles - Lina Aulia; Almirah Amanda Putri; M Zaky Hadi (LPPMPK- Universitas Muhammadiyah Cileungsi, 2024)
The purpose of this study is to standardize the workplace to meet CV ND Konveksi's goals for working hours. The variety of t-shirt production process timings at CV ND Konveksi, the unknown production process time for each type of t-shirt, and the nonconformity of Standard Operational Procedures (SOP) with actual work techniques are all impacted by current work environment issues. Using process activity mapping, observations were conducted of every step in the t-shirt production process to gather data for the study. By classifying the value of operations into three categories—value added, no value added, and no value added but necessary—the outcomes of data processing are assessed. Root Cause Analysis (RCA) is used to perform a root cause analysis based on the activity categories whose values have been determined. The identification of the root cause of the issue was based on the source of the problem that was experienced. This root cause was the absence of standardization in the work environment, which led to the formation of wasteful practices such as searching. The 5S principle (seiri, seiton, seiso, seiketsu, and shitsuke) is applied in the work environment standardization strategy. When CV ND Konveksi Lampung adopted the 5S program, performance productivity increased by 10%, the value ratio decreased by reducing NNVA activities by 22 and NVA by 13, and the processing time efficiency increased by 30%, from 19.7 minutes to 13.9 minutes for the production of a single t-shirt. Another result was activity efficiency, which came in at 22%. Of the activities, 15 could be deleted because they contributed no value